THE PHENOLOGY OF OCCURRENCE OF DOMINANT PREDATORY SYRPHIDAE (DIPTERA) SPECIES IN APPLE ORCHARDS AND ON THEIR EDGES - Hanna Piekarska-Boniecka; Idzi Siatkowski; Joanna Zyprych-Walczak; Paweł Trzciński; Marta Rzańska-Wieczorek (Acta Scientiarum Polonorum: Hortorum Cultus, 2017)
The blooming wild plants in the vicinity of orchards may attract adult Syrphidae to these cultivations. Hence in 2008–2010 studies were conducted around Czempiń (western Wielkopolska) which covered the occurrence of the imagines of 5 dominant predatory Syrphidae species in apple orchards and on their edges. The phenology of Episyrphus balteatus (De Geer), Eupeodes corollae (F.), Melanostoma mellinum (L.), Sphaerophoria scripta (L.) and Syrphus vitripennis Meigen in apple orchards as well as in the neighbouring shrubberies and on the side of the road overgrown with trees and bushes was analysed. A greater abundance of imagines of the studied species was found on the edges than in the apple orchards. Also a preference for either orchards or their sides was indicated for Syrphidae, as they appeared in these biocenoses earlier or later, but not at the same time. A correlation between a mass catch of Syrphidae in the orchards and their edges was found. It was shown that the blooming plants of orchard edges, such as Tilia cordata, Symphoricarpos albus, Cirsium arvense and Galium aparine, could attract Syrphidae imagines to the orchards.